FATHER–CHILD INTERACTIONS AT 3 MONTHS AND 24 MONTHS: CONTRIBUTIONS TO CHILDREN'S COGNITIVE DEVELOPMENT AT 24 MONTHS. Issue 3 (27th April 2017) - Sethna, Vaheshta; Perry, Emily; Domoney, Jill; Iles, Jane; Psychogiou, Lamprini; Rowbotham, Natasha E.L.; Stein, Alan; Murray, Lynne; Ramchandani, Paul G.
ABSTRACT: The quality of father–child interactions has become a focus of increasing research in the field of child development. We examined the potential contribution of father–child interactions at both 3 months and 24 months to children's cognitive development at 24 months. Observational measures of father–child interactions at 3 and 24 months were used to assess the quality of fathers' parenting ( n = 192). At 24 months, the Mental Developmental Index (MDI) of the Bayley Scales of Infant Development, Second Edition (N. Bayley, 1993 ) measured cognitive functioning. The association between interactions and cognitive development was examined using multiple linear regression analyses, adjusting for paternal age, education and depression, infant age, and maternal sensitivity. Children whose fathers displayed more withdrawn and depressive behaviors in father–infant interactions at 3 months scored lower on the MDI at 24 months. At 24 months, children whose fathers were more engaged and sensitive as well as those whose fathers were less controlling in their interactions scored higher on the MDI. These findings were independent of the effects of maternal sensitivity. Results indicate that father–child interactions, even from a very young age (i.e., 3 months) may influence children's cognitive development. They highlight the potential significance of interventions to promote positive parenting by fathers and policies that encourage fathers to spend more time with their young children.